Prediction of carcass composition from measurements of wholesale carcasses - Žgur, Silvester; Majer, M.; Čepon, Marko (Acta Agraria Kaposváriensis, 1999)
Carcass data from 238 brown bulls were analysed to estimate the possibilities for prediction of carcass composition from measurements of wholesale carcasses. Measurements included carcass weight, carcass length, chest depth, longissimus dorsi muscle area between the 7th and 8th ribs and carcass conformation and fatness notes. Actual tissues weights and proportions were obtained from carcass dissection into lean, fat, tendon and bone. Using carcass weight, carcass length, chest depth, EUROP conformation and fatness notes, it was not possible to accurately predict proportion of carcass tissue of progeny tested Brown bulls (r2 of 0.142, 0.104, 0.061, 0.230 for lean, fat, tendon and bone). Also inclusion of longissimus muscle area did not significantly improve the coefficient of determination. Accuracy of predicting carcass tissue weight was higher, (r2 of 0.867, 0.191. 0.076, 0.355 for lean, fat. tendon and bone), but only the prediction of lean weight was sufficiently accurate.